Reduced reproductive potential in young healthy women with hereditary breast and/or ovarian cancer syndrome - Giovanna Sighinolfi; Giovanni Grandi; Elena Barbieri; Marta Venturelli; Claudia Piombino; Chiara Melotti; Rebecca Lippi Bruni; Riccardo Costantini Cuoghi; Roberto D’Amico; Matteo Lambertini; Fedro A. Peccatori; Elena Tenedini; et al. (Communications Medicine)
Abstract Background Young, healthy women carrying a pathogenic or likely pathogenic variant (P/LPV) in genes configuring the hereditary breast and/or ovarian cancer (HBOC) syndrome face several non-oncological issues. Among these, the implications on fertility are not yet entirely understood. Methods Aiming to explore the ovarian reserve in young, healthy women with HBOC syndrome, we conducted a monocentric, prospective, observational cohort trial between January 2020 and September 2023. Eighty-seven healthy women aged less than 42 years with a P/LPV in HBOC predisposition genes were enrolled: 32 BRCA1 P/LPV carriers, 47 BRCA2 P/LPV carriers, and 8 carriers of P/LPV in other genes (TP53, RAD50, CHECK2, RAD51D, PALB2, ATM). AMH levels and antral follicular count (AFC) were evaluated as fertility biomarkers. Results No significant differences in demographic characteristics or mean levels of AMH or in AFC are observed between BRCA1 and BRCA2 P/LPV carriers. The distribution of AMH values is significantly lower compared to the general population (p = 0.019). The significant decrease in AMH levels is mostly ascribable to BRCA1 P/LPV carriers (p = 0.03). Both in the overall population and in BRCA1/2 P/LPV carriers, AFC decreases faster compared to those reported in the nomogram. Conclusions A consistent trend for reduced reproductive potential in young, healthy women with HBOC syndrome is observed, particularly in BRCA1 P/LPV carriers. These findings need to be confirmed by larger studies including also women carrying P/LPV in other HBOC syndrome-related genes.